Technical Actions in Volleyball Protection - Joldasbaeva Aziza Begis qizi; Bektursinova Uldawlet Orazbay qizi (Genius Journals, 2022)
This article presents technical devices that allow the study of time parameters specific to the game of volleyball. The positions of the players of the defending team developed by the authors are given.
Keywords: Volleyball; defense; attack; efficiency